1999
DOI: 10.1046/j.1365-2788.1999.043005393.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of aggression, and adaptive and maladaptive behaviour in older people with Down’s syndrome with and without dementia

Abstract: In a cross-sectional study of aggression, and adaptive and maladaptive behaviour in 128 subjects with Down's syndrome (DS), 29 of whom had dementia, the current authors found that the presence of dementia was not predictive of aggression or maladaptive behaviour. However, the level of adaptive behaviour was shown to be lower in subjects with dementia, and in those with lower levels of cognitive functioning, as measured on a rating instrument, the Test for Severe Impairment. Although the presence of aggressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…It takes 10 minutes to administer. Only eight of the 24 points on the TSI require a verbal answer, which is beneficial when testing people with poor verbal ability (Cosgrave et al, 1999). The TSI has been validated in the DS population, and reliability and validity assessed by Cosgrave et al, (1998).…”
Section: Direct Cognitive Assessment Of An Individualmentioning
confidence: 99%
“…It takes 10 minutes to administer. Only eight of the 24 points on the TSI require a verbal answer, which is beneficial when testing people with poor verbal ability (Cosgrave et al, 1999). The TSI has been validated in the DS population, and reliability and validity assessed by Cosgrave et al, (1998).…”
Section: Direct Cognitive Assessment Of An Individualmentioning
confidence: 99%
“…Aggression occurred with greater frequency in the subjects with intellectual disability due to other causes. Cosgrave et al, (1999) reported that the presence of dementia is not predictive of aggression or maladaptive behaviour. However, the level of adaptive behaviour is lower in subjects with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Cosgrave et al (2000) demonstrated the validity, test-retest reliability, and inter-rater reliability of the TSI in DS populations with comorbid ID. The TSI may be especially beneficial for individuals with poor verbal skills as only eight items require verbal responding (Cosgrave et al 1999).…”
Section: Direct Assessmentmentioning
confidence: 99%